PELAKSANAAN PERJANJIAN PEMBIAYAAN KONSUMEN DALAM JUAL BELI KENDARAAN BERMOTOR - Anggraini Kosasih; Henny Arianty Simanjuntak; Rima Afrida; Suhaila Zulkifli (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Consumer finance is one of models of finance which by a consumer it can be used forapplying for a loan to a finance company. The objective of this study is to know the consumer finance, with right and obligation of parties concerned and the legal consequences if one party defaults. This study is normative juridical research because it takes resources of data either primary, secondary, and as well as tertiary law. All the data were collected by library research and by agreement point to consumer finance. The data analysis is done qualitatively. The original consumers finance come out promises with contract between one party to other that resulted in a mutual agreement. The consumer finance has been regulated officially as in the regulations of Presidential decree Peraturan Presiden Republic Indonesia No. 9 of 2009 on a Finance Agency, it noted the rights and obligation of the parties involved for it is usually made in an agreement letter as consumer finance. So, any right and obligation of those parties should be determined by consumer finance agent itself refers to the regulation applied in Indonesia. For any default done by one in any party, it is possible to file a lawsuit to court.